What a hard decision: Capital structure of reits in Istanbul stock exchange - AYBARS, ASLI (My University, 2023)
By examining the factors that determine the capital structure for Turkish Real Estate Investment Trusts (REITs) in Borsa Istanbul (BIST) over the period 2014-2020, we attempt to present a contribution to the capital structure literature. In our study, we use panel data analysis that provide us proofs about the impact of financial performance, stock performance, and corporate structure on capital structure decisions of REITS. Some of the findings are remarkably similar to those of prior studies in this array of literature while our independent variables and capital structure may seem to be connected differently from the leading capital structure theories (\"pecking order theory and trade-off theory\"). The prominent capital structure theories of pecking order and trade-off theory likewise receive mixed support, although the link between capital structure and our independent variables appears to be skewed. As a result, the theory’s assumptions indicate that capital structure changes are driven by survival.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); REIT; Debt ratio; ISE; Trade-off Theory; Pecking Order Theory; Capital Structure; Turkey